2020
DOI: 10.1038/s42005-020-00443-w
|View full text |Cite
|
Sign up to set email alerts
|

Transversally travelling ultrasound for light guiding deep into scattering media

Abstract: The application of optical methods for tissue diagnosis, activation, and treatment suffers dramatically from the low accessible depths due to strong light scattering in tissues. Here we demonstrate a method to address this issue by utilizing transient ultrasound waves, travelling transversally to the light propagation direction, to guide light into deeper tissue regions. We study the formation of the ultrasound-induced refractive index structures and waveguides using simple ultrasound field configurations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…However, acousto-optic modulation helps to overcome this limitation, allowing the delivery or collection of light without confinement to shallow depths of the turbid medium. Existing acousto-optic modulation techniques form virtual waveguides within tissues using standing waves, which require the object to be situated inside an ultrasonic device (19)(20)(21)(22). The constraints imposed by the physical structure of the device hinder its application in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…However, acousto-optic modulation helps to overcome this limitation, allowing the delivery or collection of light without confinement to shallow depths of the turbid medium. Existing acousto-optic modulation techniques form virtual waveguides within tissues using standing waves, which require the object to be situated inside an ultrasonic device (19)(20)(21)(22). The constraints imposed by the physical structure of the device hinder its application in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Since ultrasound in the proper frequency range can propagate deep with minimal attenuation in the medium, the virtual optical components can be realized within the target medium to manipulate the trajectory of light without implanting any physical devices to disturb the medium. We have shown that these linear virtual optical components can be formed in transparent as well as scattering media such as biological tissue 12 . In this method, the virtual optical component can be reconfigured by simply changing the pattern of ultrasound waves from outside the medium.…”
Section: Introductionmentioning
confidence: 98%
“…We have recently shown that ultrasound waves can be used to guide and pattern the trajectory of light by locally changing the refractive index of the medium. Using this technique, we have demonstrated the possibility of forming in situ virtual gradedindex (GRIN) waveguides, virtual relay lenses, and spatial light modulators non-invasively [12][13][14] . Since ultrasound in the proper frequency range can propagate deep with minimal attenuation in the medium, the virtual optical components can be realized within the target medium to manipulate the trajectory of light without implanting any physical devices to disturb the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual optical waveguides can be implemented using ultrasonic waves from phased arrays [1], transient ultrasonic waves [4], and laser-induced nonlinear acoustic waves [5]. These implementations can be useful in a variety of applications that require in situ light steering.…”
Section: Introductionmentioning
confidence: 99%